2020
DOI: 10.17485/ijst/2020/v13i08/149808
|View full text |Cite
|
Sign up to set email alerts
|

Big Data and the Future of the Accounting Profession

Abstract: Background/objectives: The purpose of this research is to study and analyze the Big Data, to identify the challenges which facing Big Data in business organizations, and to clarify the impact of Big Data on changing the roles of accountants and accounting profession. Determining the impact of big data analysis on improvement accounting information quality. Methods/statistical analysis: To achieve this objective, reference was made to previous studies and related research, with a qualitative study based on in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Accounting students' education should take a much broader approach and go beyond conceptual and technical accounting knowledge. Future accountants must be aware of the importance of Big Data through increasing their ability and skills to interpret and analyse Big Data to add value to business organisations (Younis, 2020). Results on a survey by Jackling and De Lange (2009) on 650 accounting graduates as well as 28 professionals showed that both groups agreed on the importance of technical skills.…”
Section: Big Data Analytics Within Accounting Educationmentioning
confidence: 99%
“…Accounting students' education should take a much broader approach and go beyond conceptual and technical accounting knowledge. Future accountants must be aware of the importance of Big Data through increasing their ability and skills to interpret and analyse Big Data to add value to business organisations (Younis, 2020). Results on a survey by Jackling and De Lange (2009) on 650 accounting graduates as well as 28 professionals showed that both groups agreed on the importance of technical skills.…”
Section: Big Data Analytics Within Accounting Educationmentioning
confidence: 99%
“…Behavioural reasoning theory [18] offers a paradigm in which user interaction is essential to effective technology adoption. Users with a propensity for change accept new technology with less opposition [19], [20]. Different perspectives influenced the adoption of new technology [21].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…From the perspective of IT organizations, decision support systems (DSS), business intelligence (BI), and acquisition of BD&A technologies, both technology, and organizational capabilities, are needed to ensure successful implementation [19], [20]. [32] agree that facilitating conditions affect intentions leading to adoption in BD&A and other emerging IT Regarding mediation, the intention of use may affect the behaviour of website users.…”
Section: Facility Conditionmentioning
confidence: 99%
See 1 more Smart Citation